Targeted Interventions : India’s Pathbreaking Approach to Address the HIV/AIDS Pandemic - Mohammed, Suresh Kunhi; Mutasa, Ronald Upenyu; Mehta, Ishira (World Bank, Washington, DC, 2021)
This case study documents how India, the world’s second most populous country, pulled the reins on a global epidemic to stop it in its tracks from growing into a generalized epidemic. Central to the case study is the story of a government body, the National AIDS Control Organization (NACO) that, with the support of international development organizations like the World Bank, deftly collaborated with civil society organizations to engage with communities that had a high risk of HIV infection and were also highly marginalized to implement large scale behavior change in the interest of individual and public health. Above all, this is a story of courage, resilience and gumption of some of the most hidden and disenfranchised communities of India in taking charge of their destinies with respect to HIV-AIDS and demonstrating that if provided with the right programmatic structure and a supportive ecosystem, they can rise towards a better tomorrow. This case study is the story of India’s fight against HIV-AIDS and the significant role played by Targeted Interventions in this fight. Targeted Interventions are a resource-effective approach to offer HIV prevention and care services to high-risk populations within communities by providing them with the information, means and skills they need to minimize HIV transmission and improving their access to care, support and treatment services.